Development of a Case Formulation Model for Individuals Who Have Viewed, Distributed, and/or Shared Child Sexual Exploitation Material - Merdian, Hannah L. (International journal of offender therapy and comparative criminology, 2020)
Increases in the number of arrests of individuals who download or distribute Child Sexual Exploitation Material (CSEM) have highlighted a need to further understand the offending pathways of this offender group. This article describes the development of an aetiological model specific to CSEM offending. Individuals who had viewed, distributed, and/or shared CSEM (n = 20) were interviewed regarding their life and sexual history, relationships, substance use, offending details, and circumstances leading to their CSEM offending, resulting in seven superordinate themes: Developmental Context, Individual Propensities (risk-related and risk-protective) and Psychological Vulnerabilities, Personal Circumstances, Permission-Giving Thoughts, Internet Environment and Behaviour, Evaluation of Consequences for the Individual, and Desistance. These themes were combined into a case formulation tool specific for CSEM offending behaviour, with the aim of providing systematic guidance for assessment and treatment providers.